Pelaksanaan Identifikasi dan Asesmen Bagi Anak Berkesulitan Belajar di SD Negeri 63 Surabayo Lubuk Basung Kabupaten Agam - Putri, Yuliana; Sopandi, Asep Ahmad (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2019)
This study based on to find out and describe the identification and assessment design, implementation of identification and assessment, evaluation of identification and assessment for children with learning disabilities in SD Negeri 63 Surabayo Lubuk Basung Kabupaten Agam. This study used a descriptive research method with a qualitative approach conducted at SD Negeri 63 Surabayo Lubuk Basung Kabupaten Agam. The research subjects are Special Education Teachers (SET). The technique of collecting data uses are observation, interviews and documentation. The validity of the data is tested using triangulation techniques. The results of this study indicate that the process of identifying learning difficulties is carried out by classroom teachers, then the problematic identified students are reported to special education teachers, after that special education teachers at the school with the source center special education teachers work together to carry out the assessment. After the assessment process has been completed, the center's special education teacher will prepare an individual learning program which will be given to special education teachers and classroom teachers of each difficulty learning students to carry out.